The Ethanol Extract of Lonicera japonica (Japanese Honeysuckle) Attenuates Diabetic Nephropathy by Inhibiting p-38 MAPK Activity in Streptozotocin-Induced Diabetic Rats - Tzeng, Thing-Fong; Liou, Shorong-Shii; Chang, Chia Ju; Liu, I-Min (Planta Medica, 2014)
The anti-inflammatory potential of Lonicera japonica makes it an excellent source of novel medicinal targets to reduce inflammation in diabetic nephropathy. We aimed to investigate whether the ethanol extract of the flowering aerial parts of L. japonica exerts an ameliorative effect on diabetic renal inflammation using streptozotocin-induced diabetic rats. Diabetic rats were treated orally with the ethanol extract of the flowering aerial parts of L. japonica (100 and 200 mg/kg/day) for 8 weeks. The rats exhibited renal dysfunction, as evidenced by reduced creatinine clearance, increased blood urea nitrogen, and proteinuria, along with a marked elevation in the ratio of kidney weight to body weight; all of these abnormalities were significantly reversed by the ethanol extract of the flowering aerial parts of L. japonica. The histological examinations revealed amelioration of diabetes-induced glomerular pathological changes following treatment with the ethanol extract of the flowering aerial parts of L. japonica. It reduced the accumulation of ED-1-expressing macrophages in renal tissue of diabetic rats, almost completely abolished T cell infiltration and attenuated the expression of proinflammatory cytokines. The ethanol extract of the flowering aerial parts of L. japonica downregulated the protein expression of p38 mitogen-activated protein kinase in the kidney of diabetic rats. The results suggest that it has the property to inhibit the activity of p-38 MAPK-mediated inflammatory response to halt the progression of diabetic nephropathy.
Keywords: diabetic nephropathy; diabetic rats; inflammatory response; Lonicera japonica; Caprifoliaceae; p-38 MAPK